Stalked by the Malignant Father's Spirit: A Case of Patricide among the Yagwoia (PNG). - Mimica, Jadran (Oceania, 2023)
Among the Yagwoia (PNG), the dynamics of fatherhood is a process of man's transmission to and incorporation of his vital substance by his progeny. In this way, the father becomes replaced principally by his son(s). This process, referred to as the incorporation and replacement of the father's 'bone', has multiple actualisations whose concrete reality and significance can only be adequately understood through individual‐biographical life‐situations and trajectories. Even if not expressed through overt conflict, the dynamics of the incorporation of the father's 'bone' is fundamentally conflictual. It is frequently experienced by man as a violent loss of and disinvestment from his generative bodily core, especially in the sphere of prestations and financial provisioning for his children. In this context, the father's handling of his son's bride‐price shells/money has central importance. However, it is the entirety of the father's comportment to his son and daughter that effectively generates this continuous and irreversible process of the self‐transmission of his vital substance. If he is greedy, selfish and ungiving, then all the same – his 'bone' transmission will be merely keyed in and acted out in an increasingly overt negative mode, and the son's comportment to him will be equally bad. No matter what kind of father a man may be, his son's incorporation of his father's osseous strength is unstoppable. Thus, a son not only threatens and intimidates, but also may beat up and occasionally kill his father. This paper deals with one such extreme case of son's replacement and incorporation of his father's vital core.